Creative Parameters for Adult Active Web Users - Elena Medvedskaia (Проблеми сучасної психології, 2020)
The aim of the article is to analyze empirical data that test the hypothesis of greater creativity of active Internet users compared to adult fans of traditional reading. Methods. The study was conducted on a statistically large and homogeneous sample by age, level of education and professional activity (the sphere of mental work). The differentiation of respondents into groups for comparative analysis was carried out on the basis of two criteria: 1) the choice of information system in free time (book or Internet); 2) the time allocated to work with the specified system. The criteria were determined through anonymous and voluntary questionnaires. The parameters of creativity were measured for different types of creativity: verbal (Mednik’s test in the adaptation of A. A. Voronin) and figurative (Sievert’s test). The research presents the results of the comparative analysis conducted in two contrasting groups that select different information systems: subjects of reading and active web users. Statistically significant advantages of reading subjects in the expression of most of the measured parameters of both verbal (uniqueness and number of responses) and figurative (uniqueness and number of associations from remote areas) creativity were established. Conclusions. It is empirically proved that there are significantly more creative people among fans of traditional printed books. This demonstrates that the technical capabilities of the Internet (the richness of content, the possibility of free choice of content and participation in its creation, etc.) do not automatically provide conditions for the display of creative abilities of users. An explanation is offered for the lower creativity of adult active web users through the specifics of the media image as the main unit of encoding information in digital media (the iconic nature of information and the suggestiveness of impact).